Pengaruh Bahasa Indonesia sebagai Alat Komunikasi dalam Bisnis Internasional di Era Digital - Ika Febriana; Febri Br Hutabarat; Mery Kristiani; Rina Rina; Salma Diani; Uswatul Akmalia (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This article examines the role of Indonesian as a communication tool in international business in the digital era. This topic is important given Indonesia's economic growth and its potential in the global market, particularly in Southeast Asia. The research uses a literature review method, analyzing relevant sources related to the use of Indonesian in the context of international business. Opportunities that can be leveraged include the growth of e-commerce and the potential of Indonesian as a lingua franca in Southeast Asia. The study concludes that with the right strategies, Indonesian can become an effective communication tool in international business, opening opportunities for Indonesian companies in the global market and helping foreign companies adapt to the Indonesian market.